A new way of doing research for Agricultural development - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Alain Vidal, Program Director, CGIAR Challenge Program on Water & Food speaking on a new approach to research for Agricultural development The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/... http://www.fara-africa.org/scienceweek/